2018
DOI: 10.22478/ufpb.1981-1268.2018v12n2.37091
|View full text |Cite
|
Sign up to set email alerts
|

Potencial alelopático do extrato etanólico de Anacardium humile (cajuzinho-do-cerrado) na germinação e formação de plântulas de alface, tomate e fedegoso

Abstract: O gênero Anacardium, Anacardiaceae, destaca-se em relação aos demais gêneros desta família devido à presença de compostos fenólicos, que possuem inúmeras aplicações e usos populares. Uma das espécies, investigada pelos diferentes usos e potencialidades de utilização, é Anacardium humille (cajuzinho-do-cerrado). Porém pouco se sabe sobre sua ação alelopática. Desta maneira, o presente trabalho teve por objetivo qualificar a composição química das folhas e avaliar os possíveis efeitos alelopáticos do extrato eta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
3
6
0
1
Order By: Relevance
“…Mart., also reported that tomato seeds were more affected than lettuce seeds, demonstrating their greater susceptibility to the metabolites, interfering with both seed germination and seedling growth. The action potential of the aqueous extract of stem and leaves of A. humile has previously been reported by Periotto et al (2012) and Pereira et al (2018), who observed negative effects on the seed germination and seedling growth in lettuce and radish (Raphanus sativus L.), corroborating the findings of this study.…”
Section: Germination Bioassayssupporting
confidence: 92%
See 1 more Smart Citation
“…Mart., also reported that tomato seeds were more affected than lettuce seeds, demonstrating their greater susceptibility to the metabolites, interfering with both seed germination and seedling growth. The action potential of the aqueous extract of stem and leaves of A. humile has previously been reported by Periotto et al (2012) and Pereira et al (2018), who observed negative effects on the seed germination and seedling growth in lettuce and radish (Raphanus sativus L.), corroborating the findings of this study.…”
Section: Germination Bioassayssupporting
confidence: 92%
“…Despite the large number of studies addressing the allelopathic effects of plant extracts on seed germination and seedling growth, few have analyzed the correlation between presence of secondary metabolites and their intensity, seed germination and vigor, and seedling growth. Among these, the studies by Oliveira et al (2011Oliveira et al ( , 2013, Rizzi et al (2016), Matias et al (2017Matias et al ( , 2018 and Pereira et al (2018) should be highlighted, as they confirm the results obtained in the present study, in which the presence of metabolites interfered in different ways with the germination and growth processes. The aforementioned authors verified that certain metabolites, such as phenolic compounds, flavonoids, cardioactive heterosides and saponins, are responsible for the allelopathic action observed, negatively affecting seed germination and seedling growth.…”
Section: Germination Bioassayssupporting
confidence: 89%
“…Aqueous extract presented a lower frequency of secondary metabolites, being 50% for alkaloids, phenolic compounds, flavonoids and saponins; only the saponins showed a higher frequency in relation to ExtEtOH (Figure 1). The use of ethanol as an effective solvent for the extraction of phytochemicals has also been reported by Pereira et al (2018), working with leaves of Anacardium humille A.St.-Hil, and reporting the presence of eight classes of metabolites. Vernay et al (2008) also pointed out alkaloids as major constituents in the leaves of D. inoxia, a specimen grown in France.…”
Section: Resultsmentioning
confidence: 92%
“…In general, the effects caused by allelochemicals tend to be concentration-dependent, that is, they tend to be more pronounced at higher concentrations, and this tendency is observed in the initial growth bioassays in recent studies with leaf extract of Kielmeyera coriacea, Canavalia ensiformis and Anacardium humile, on L. sativa (Santos et al, 2015;Pereira et al, 2018;Matias et al, 2018).…”
Section: Resultsmentioning
confidence: 96%